2013
DOI: 10.1155/2013/207308
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Osmotic Dehydration of Cranberries under Continuous Flow Medium Spray Conditions

Abstract: Microwave-osmotic dehydration of cranberries was evaluated under continuous �ow medium spray (MWODS) conditions aer some pretreatments. A central composite rotatable design was used with three input variables at �ve levels (temperature, 33 ∘ C-67 ∘ C; sucrose concentration, 33 ∘ B-67 ∘ B; and contact time, 5-55 min). Responses were moisture loss (ML), solids gain (SG), and weight reduction (WR) as well as color and texture parameters. e responses were related to process variables using response surface metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
(61 reference statements)
2
26
0
Order By: Relevance
“…[22] Therefore, IQF whole cranberries (Atoka Cranberries Inc., Manseau, QC, Canada) were kept frozen (À21 to À27 C) until use, at which point the berries were thawed by floating %200 g batches of berries in approximately 2 L of room temperature tap water for 1 h as previously described. [22] During this time, the berries were sorted, where only whole, undamaged, and ripe cranberries of medium size (approximately 10-15 mm diameter) were selected and underripe (white), broken, crushed, or otherwise damaged berries were discarded. Samples were then blotted to remove surface moisture before being weighed and transferred either directly to the MWV setup or first to the MWODS pretreatment.…”
Section: Materials and Methods Cranberriesmentioning
confidence: 99%
See 3 more Smart Citations
“…[22] Therefore, IQF whole cranberries (Atoka Cranberries Inc., Manseau, QC, Canada) were kept frozen (À21 to À27 C) until use, at which point the berries were thawed by floating %200 g batches of berries in approximately 2 L of room temperature tap water for 1 h as previously described. [22] During this time, the berries were sorted, where only whole, undamaged, and ripe cranberries of medium size (approximately 10-15 mm diameter) were selected and underripe (white), broken, crushed, or otherwise damaged berries were discarded. Samples were then blotted to remove surface moisture before being weighed and transferred either directly to the MWV setup or first to the MWODS pretreatment.…”
Section: Materials and Methods Cranberriesmentioning
confidence: 99%
“…[21,22] The only variation to the setup was the use of a new spray head (model RPB-173C, Waterpik Technology Inc., Markham, ON, Canada) instead of the now-discontinued model that was used previously. The RPB-173C was chosen because its diameter matches that of the sample container (12.5 cm) and due to its even spray distribution over the entire area of the sample stage.…”
Section: Mwods Pretreatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,59] Moreover it was found that MWV dried samples showed softer texture and were less tough that convective dried berries, where additional benefits were noted in terms of energy efficiency. [1] As opposed to solely as a finish drying method, microwaves have more recently been applied during osmotic dehydration, in either immersion [136] or spray [89,[137][138][139][140][141][142] based configurations. Initially [136] it was found that apple cylinders that were exposed to microwave energy while submerged in a continuous flow of osmotic syrup had improved moisture transfer rates when compared to conventional osmotic dehydration (COD), while solids gainwas reduced compared to prior studies using both traditional static batch [143] and continuous flow [144] conditions in the same experimental setup.…”
Section: Microwave Drying and Osmotic Dehydrationmentioning
confidence: 99%